Resection of a mature giant teratoma with clamshell incision thoracotomy approach: Case report and literature review - Adhyasta Nata Prawira Subianto; Maz Isa Ansyori Arsatt (DiscoverSys Inc., 2022)
Introduction: Resection of giant teratomas can be challenging. An advanced surgical technique should be designed to ensure surgical safety and complete removal of giant teratomas. We describe a case of a mature giant teratoma successfully resected with a clamshell incision thoracotomy approach. Case Description: A female, 11 years complained of shortness of breath for the last two weeks before being admitted to the hospital. Physical examination revealed a retraction of the patient's chest wall, decreased breath sounds in the left lung field, and dull percussion in the left lung field. Chest CT scan with contrast was carried out with a minimal right pleural effusion with mediastinal mass size 14 x 17 x 16 cm. The patient underwent surgery to extract the mediastinal mass; an anterior thoracotomy was performed using the Clamshell incision method on the patient's chest. Complete resection of the mass was performed. Histopathology examination was performed on the mass with the results in accordance with the description of Mature Cystic Teratoma. The patient returned home in good condition and then controlled through the outpatient polyclinic. Discussion: Clamshell incisions provide enough exposure for tumors in the mediastinum that extend into the thoracic cavity. For complete removal of a gigantic teratoma, extensive surgical and visual fields are required, as in this case. Conclusion: Clamshell incisions in anterior thoracotomy give a good surgical field and can be safely performed in patients with large mediastinal teratomas.